Le competenze di cittadinanza dei volontari del Servizio Civile Universale. Uno studio empirico - Paolo Di Rienzo; Ada Manfreda (LED Edizioni Universitarie, 2022)
The paper presents the results of the research on citizenship competences of civil service operators, carried out with the participation of the Third Sector National Forum and with Arci Civil Service. The issue of citizenship competences and their enhancement is considered crucial both from the policy level and from the point of view of international studies. Eleven focus groups were conducted, aimed at volunteer operators, distributed in ten different Italian regions, for a total of 56 participants. All the discursive material produced was recorded and transcribed and made suitable to be subsequently subjected to statistical analysis, conducted in particular through correspondence analysis and cluster analysis. The choice of the method, and consequently of the tool, for the treatment and analysis of the data arose from a semiotic theoretical perspective. The data obtained from the analysis and interpretation of the speeches produced in the focus groups tell us that competence is mainly assumed as a synonym of knowledge, especially for what concerns civic competences. Even with respect to the meaning and role that the volunteer seems to assign to communication competences, the control of emotions and interpersonal skills, it seems necessary to problematize the development of these competences, considering how much the activities related to the world of volunteering have a high relational and emotional content.